Unleashing the Efficiency and Potential of Indonesian Fishery Exports to European Union Market - Khaliqi, Muhammad; Novıantı, Tanti; Wibowo, Rulianda Purnomo (Journal of Agricultural Sciences (Belgrade), 2024)
The application of the Free Trade Agreement between Indonesia and the EU is expected to be a catalyst for Indonesia’s economic growth, particularly in the trade sector. However, it was recorded that in the 2020-2022 period, there were 38 notifications received by EU countries regarding Indonesian export products. The majority of notifications are related to sanitary and phytosanitary, which is a non-tariff measure in free trade. Thus, the positive trend of imports of EU fishery commodities cannot be utilized by Indonesia. Therefore, this study was designed to fill the current research gap relating to the efficiency and export potential of Indonesian fishery products in the EU market. The purpose of this study was to analyze the factors influencing the flow of Indonesian fisheries trade, export efficiency, and the potential for Indonesian fisheries exports in the EU market using the stochastic frontier gravity model approach. This study used panel data on Indonesian fishery products exported to EU-27 countries in 2003-2021 (19 years). This study used HS 03, those which were products of fish and crustaceans, mollusks and other aquatic invertebrates which were traded by Indonesia to 25 EU countries. The estimation results showed that the GDP of the exporting country, the GDP of the importing country, competitiveness, and the exchange rate of the rupiah against the US dollar had a positive effect on exports of fishery products to the EU market. Meanwhile, distance proxied using trade cost revealed a negative effect on Indonesia’s fisheries exports in the EU market. The calculation results demonstrated that Indonesia did not have an efficiency value of 100%. The biggest market potential that Indonesia could maximize in the EU market was the export of fishery products to France, Italy, Germany, Austria, and Spain.